2003
DOI: 10.1207/s15327949pac0902_02
|View full text |Cite
|
Sign up to set email alerts
|

Whose House is This? Dilemmas of Identity Construction in the Israeli-Palestinian Context.

Abstract: This article examines the ways in which one's perception of the other contributes to processes involved in the construction of collective identity. This study presents analyses and comparisons of semi-structured interviews using a dilemma concerning ownership of a house that was undertaken with 20 Jewish and Palestinian university students, citizens of Israel, who participated in a 1-year seminar that dealt with the Palestinian-Israeli conflict. Analyses of the entire sample showed that, during the year, all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 11 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…As another example, when a Palestinian student described how her family avoided evacuation from their hometown in 1948 and then were later forced to live in a ghetto, a Jewish participant responded with the comment that her father had grown up near that ghetto and that he used to describe it very vividly in a positive way (facilitator notes of student comments). After hearing the Palestinian's story, that Jewish participant's journal entries showed that the story forced her to re‐examine the stories that she heard from her father and the reasons for the discrepancies that existed in the ways both fathers constructed their past (Litvak‐Hirsch, Chaitin, & Bar‐On, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As another example, when a Palestinian student described how her family avoided evacuation from their hometown in 1948 and then were later forced to live in a ghetto, a Jewish participant responded with the comment that her father had grown up near that ghetto and that he used to describe it very vividly in a positive way (facilitator notes of student comments). After hearing the Palestinian's story, that Jewish participant's journal entries showed that the story forced her to re‐examine the stories that she heard from her father and the reasons for the discrepancies that existed in the ways both fathers constructed their past (Litvak‐Hirsch, Chaitin, & Bar‐On, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In this workshop, young adult students were involved, not practitioners or middle‐aged descendants of the Holocaust. Although the students, like the original TRT members, had volunteered to participate in the group process, many of them had no previous experience in trying to work through the Palestinian‐Israeli conflict with people from the “other side.” These young adults were at the developmental stage in which they were still constucting their individual and collective identities (Litvak‐Hirsch, Chaitin, & Bar‐On, 2003). Perhaps for that reason, in comparison to the older members of the TRT, they were less able to reflect on the group process and its relation to the external conflict and to understand the processes that the other group was undergoing (Bar‐On, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method, which was developed in the Piaget / Kohlberg tradition, is still often used with a relatively standardized guideline in order to record how people form moral judgments (see Kohlberg 1976), but such interviews can be conducted much more openly and can be used in respect of other research question (see Aufenanger 1991;Döbert / Nunner-Winkler 1983;Hopf et al 1995;Litvak-Hirsch et al 2003;Nunner-Winkler 1989;Schuhler 1979). In particular, it is possible to use moral conflicts that might arise in the everyday experience of the interviewees, instead of the far-fetched dilemmas that were commonly used in this research tradition in earlier times, such as: "Heinz breaks into a chemist's and steals a drug that he would never be able to afford for his wife who is suffering from cancer" (Eckensberger et al 1975).…”
Section: Structure or Dilemma Interviewsmentioning
confidence: 99%
“…To build peaceful relations, it is necessary for people to respond in ways appropriate to meeting each other's needs, as proposed by the dual‐concern model of conflict (Pruitt & Kim, 2004). Realistic empathy might allow Palestinians to understand Israelis' realistic obsession with security, and Israelis to understand the Palestinian concerns with self‐determination and a recognition that they feel their home lands, including their houses, were unfairly taken from them over 50 years ago (Litvak‐Hirsch, Bar‐On, & Chaitin, 2003). It might also allow them to appreciate the resultant sense of humiliation Palestinians may feel (Lindner, 2002).…”
Section: Responding To Terrorismmentioning
confidence: 99%